The Effect of Environmental Performance and Environmental Disclosure on Return on Asset in Food and Beverage Companies on the Indonesia Stock Exchange in 2019–2021 - Erinda Aprilia; Noviana Ramadhani; Vika Triya Wahyuni; Maria Yovita R. Pandin (Jurnal Riset Akuntansi, 2023)
The goal of this study was to determine whether environmental performance and environmental disclosure have an impact on the return on assets of the food and beverage industry. The three parameters we took into consideration for this study were return on assets (ROA), environmental performance (EP), and environmental disclosure (ED). The food and beverage companies listed on the Indonesia Stock Exchange in 2019–2021 make up the study's population. Five samples of businesses are chosen using the intentional sampling approach and certain criteria and attributes. Using the hypothesis t test and the hypothesis F test to test hypotheses Analyze data using IBM SPSS Statistics 22. The findings of the hypothesis t test indicated that the relevance of the ROA is not significantly impacted by environmental performance. According to the results of the hypothesis t test, the relevance score of (0.92) ˃ 0.05 for the ROA is not substantially impacted by environmental performance. However, environmental disclosure significantly affects ROA, with a significance value of (0.002) ˂ 0.05. The results of the hypothesis F test revealed that environmental performance and environmental disclosure have a significant impact on ROA, with a significance value of (0.92) ˃ 0.05.